Clinical features of neuronal intranuclear inclusion disease with seizures: a systematic literature review - Zhang, Jinwei; Ling, Ling; Xiang, Lei; Li, Wenxia; Bao, Pengnan; Yue, Wei (Frontiers in Neurology, 2024)
Background: Infant, junior, and adult patients with neuronal intranuclear inclusion disease (NIID) present with various types of seizures. We aimed to conduct a systematic literature review on the clinical characteristics of NIID with seizures to provide novel insight for early diagnosis and treatment and to improve prognosis of these patients. Methods: We used keywords to screen articles related to NIID and seizures, and data concerning the clinical characteristics of patients, including demographic features, disease characteristics of the seizures, treatment responses, imaging examinations, and other auxiliary examination results were extracted. Results: The included studies comprised 21 patients with NIID with seizures. The most common clinical phenotypes were cognitive impairment (76.20%) and impaired consciousness (57.14%), and generalized onset motor seizures (46.15%) represented the most common type. Compared with infantile and juvenile cases, the use of antiepileptic drugs in adults led to significant seizure control and symptom improvement, in addition to providing a better prognosis. The number of GGC sequence repeats in the NOTCH2NLC gene in six NIID patients with seizures who underwent genetic testing ranged 72–134. Conclusion: The most common clinical phenotypes in patients with NIID with seizures were cognitive impairment and consciousness disorders. Patients with NIID presented with various types of seizures, with the most common being generalized onset motor seizures. Adult patients had a better prognosis and were relatively stable. The early diagnosis of NIID with seizures is of great significance for treatment and to improve prognosis.